Navigating Undergraduate Thesis Journey: Qualitative Exploration of Challenges, Strategies, and Skills in English Department Students - Yulia Rahayu, Endah; Yudi Cahyono, Bambang; Widiati, Utami; Suryati, Nunung; Pechinthorn, Komm (JEES (Journal of English Educators Society), 2025)
This study investigates the complex challenges, strategies, and skills development of English as a Foreign Language (EFL) undergraduate students during their thesis writing journey. While the undergraduate thesis represents a crucial milestone in higher education, EFL students face significant linguistic, psychological, andtechnical barriers that impact their academic progress. Using a qualitative approach and semi-structured interviews with eight undergraduate students from various Indonesian universities, this study examined their experiences in thesis writing. The research employed reflexive thematic analysis, using NVivo 15 software to process and analyze the data. The findings reveal three primary dimensions of challenges: linguistic knowledge and writing competence, psychological and emotional barriers, and resource-related technical constraints. Students employed various adaptive strategies, including self-management techniques, technological assistance, and comprehensive support networks to overcome these challenges. The study also identified the development of essential competencies in research methodology, critical thinking, and time management. The results highlight the need for integrated institutional support systems that address both academic and psychological aspects of thesis writing, suggesting curriculum modifications and enhanced supervision frameworks to better support EFL students in their academic journey.HIGHLIGHTS: EFL undergraduate students face three interconnected challenges during thesis writing:linguistic barriers (grammar, academic vocabulary, coherence), psychological obstacles(stress, isolation, imposter syndrome), and resource-technical constraints (limited accessto materials, technological difficulties). Successful thesis completion relies on adaptive strategies including structured self-management techniques, technological tools (AI writing assistants, referencemanagement software), and comprehensive support networks (supervisors, peers, family)that address both academic and emotional needs. The thesis writing journey develops essential transferable competencies beyond academicwriting, including advanced research skills, critical thinking abilities, and timemanagement proficiency that prepare students for future scholarly and professionalendeavors.